PENGARUH SOCIAL MEDIA MARKETING INSTAGRAM, KUALITAS PRODUK DAN KERAGAMAN MENU TERHADAP KEPUTUSAN PEMBELIAN PADA KEDAI KOPI MINIMAXX KOTA KEDIRI - Fadilla Safitri; Sri Wahyuni Mega; Lina Saptaria (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2023)
This research aims to determine the influence of social media marketing (Instagram), product quality, and menu diversity on purchasing decisions at the Minimaxx Coffee Shop, Kediri City. The research method used is a quantitative method with a descriptive approach. Data collection in this research was carried out by distributing questionnaires to consumers of the Kediri City Minimaxx Coffee Shop and calculated using the SPSS Version 25 application. Data analysis techniques used included Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, t Test, Test F, and the Coefficient of Determination Test R2. In the Validity Test, it is known that all question items (X1, X2, X3, and Y) have a significance value of 0.000 < 0.05 so that each variable is declared valid. Then in the Reliability Test each variable was declared reliable because it had a Cronbach's Aplha value > 0.60. Then in the t test it is known that the variables social media marketing (Instagram) (X1), product quality (X2), menu diversity (X3) have a significance value of 0.000 < 0.05 so that these three variables partially have a significant effect on purchasing decisions. Then the F test shows that the results of the significance value are 0.000 < 0.05, which shows that social media marketing (Instagram), product quality and menu diversity simultaneously influence purchasing decisions at the Minimaxx Coffee Shop, Kediri City.